Impacts of Ukraine Crisis on Household Consumption in Yemen and Egypt - Kurdi, Sikandra (2023)
Sikandra Kurdi IFPRI-AMIS SEMINAR SERIES Ukraine One Year Later: the impact of the war on agricultural markets and food security Co-organized by IFPRI and Agricultural Market Information System (AMIS) MAR 8, 2023 - 9:00 TO 10:30AM EST